Peran manajemen strategi dalam meningkatkan daya saing bca melalui inovasi digital di industri perbankan nasional - Ramadhan, Azhar Zahira (Maliki Interdisciplinary Journal, 2025)
The banking industry in Indonesia is undergoing significant changes driven by rapid digital transformation. PT Bank Central Asia (BCA), as one of the largest banks, faces challenges to continuously innovate in the digital era. This research aims to explore the role of strategic management in driving digital innovation at BCA and to analyze the impact of such innovation on the bank’s competitiveness in the national banking market. A descriptive qualitative approach through literature review is used to understand the concepts and phenomena faced by BCA. The findings reveal that digital innovations such as API development, mobile banking, and the use of artificial intelligence and robotics have enhanced operational efficiency and customer satisfaction, while strengthening BCA’s competitive position. These insights are expected to provide strategic recommendations for banks to optimize digital transformation and maintain a competitive edge.